2016
DOI: 10.9775/kvfd.2015.14414
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on Usage of Frozen Rumen Fluid with Adding Dimethyl Sulfoxide and Different Freezing Methods for Determination of in Vitro Digestibility

Abstract: Bu çalışmada, rumen sıvısı kaynağı olarak; taze rumen sıvısı, sıvı azot içerisinde dimetilsülfoksit (DMSO) katkısız ve katkılı (%5), derin dondurucuda DMSO katkısız ve katkılı (%5) dondurulmuş rumen sıvısı kullanılmıştır. Çalışmada 4 farklı kaba yem (mısır silajı, yonca kuru otu, mercimek samanı, buğday samanı), 4 farklı karma yem (sığır besi yemi, sığır süt yemi, toklu besi yemi ve buzağı büyütme yemi) ve 4 farklı yem hammaddesi (arpa, mısır, pamuk tohumu küspesi, soya küspesi) yem materyali olarak kullanılmı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Denek et al. ( 2016 ) showed that frozen rumen fluid had significantly reduced numbers of protozoa and anaerobic bacteria compared with fresh rumen fluid. Thus, fresh rumen fluid should be used for in vitro experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Denek et al. ( 2016 ) showed that frozen rumen fluid had significantly reduced numbers of protozoa and anaerobic bacteria compared with fresh rumen fluid. Thus, fresh rumen fluid should be used for in vitro experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The digestion of bacteria, such as anaerobic bacteria and protozoa, plays an important role in ruminant nutrition. Denek et al (2016) showed that frozen rumen fluid had significantly reduced numbers of protozoa and anaerobic bacteria compared with fresh rumen fluid.…”
Section: Rfps and Bccmentioning
confidence: 99%